2003
DOI: 10.1016/s0378-4371(02)01503-0
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of the phase clouds and statistical effects of the non-Markovity in chaotic time series of human gait for healthy people and Parkinson patients

Abstract: In this work we develop a new method of diagnosing the nervous system diseases and a new approach in studying human gait dynamics with the help of the theory of discrete non-Markov random processes [31]- [34]. The stratification of the phase clouds and the statistical non-Markov effects in the time series of the dynamics of human gait are considered. We carried out the comparative analysis of the data of four age groups of healthy people: children (from 3 to 10 year olds), teenagers (from 11 to 14 year oulds),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…We found that for patients with PD, the walking time series had a tendency to change suddenly, and this was not apparent in healthy young or elderly subjects. To confirm the long-term fluctuation of gait variability of Parkinson's disease patients, several researchers have reported gait fluctuations in two-to fiveminutes walk 13,26,27) . Hausdorff et al 13) reported gait variability of PD in a five-minute walk, but they reported no such sudden change as was seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that for patients with PD, the walking time series had a tendency to change suddenly, and this was not apparent in healthy young or elderly subjects. To confirm the long-term fluctuation of gait variability of Parkinson's disease patients, several researchers have reported gait fluctuations in two-to fiveminutes walk 13,26,27) . Hausdorff et al 13) reported gait variability of PD in a five-minute walk, but they reported no such sudden change as was seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this result newly reveals a periodicity in stride time of 20-100 seconds that is related to disease severity in individuals with PD. Yulmetyev et al 27) reported that the most trustworthy information can be obtained only from low power frequencies of gait in Parkinson's disease, but they did not report the relationship between the disease severity and the power spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The method is connected with the studies of statistical non-Markov effects, long-and short-range statistical memory effects, regularity and stochastic behavior effects, and dynamic alternation of relaxation modes in the patient in various dynamic states. The study of non-Markov effects in complex systems in biology [3,4,5,6], physics [6,7,8,9], seismology [10,11], and medicine [2,12,13,14] is of special interest for correlation analysis. The scale of time fluctuations, long-range effects, discreteness of various processes and states, and the effects of dynamic alternation in the initial time series are important role in this respect.…”
Section: Introduction Parkinson's Diseasementioning
confidence: 99%
“…In recent years universal methods of statistical physics have been more often used in medicine and biology. The methods of statistical physics which have been used to research real complex systems [20,21,22,23,24,25], in the field of cardiology reveal essentially new opportunities for the analysis, diagnostics and forecasting the processes of biological ageing and diseases of a human heart. They disclose dynamic features of HRV, latent for classical medical methods of research.…”
Section: Introductionmentioning
confidence: 99%
“…This theory has already found practical application in cardiology [21], neurophysiology [22,23], the study of locomotor and sensomotor activity [22], epidemiology [24] and seismology [25].…”
Section: Introductionmentioning
confidence: 99%